2016
DOI: 10.3390/f7120301
|View full text |Cite
|
Sign up to set email alerts
|

Male Parent Identification of Triploid Rubber Trees (Hevea brasiliensis) and the Mechanism of 2n Gametes Formation

Abstract: Eight triploids were screened among offspring of the rubber tree clone GT1 × different clones by flow cytometry and chromosome counting. Twenty-five simple sequence repeat (SSR) markers were screened to identify the origin of 2n gametes, to determine the male parents of these triploids, and to evaluate the mechanism of 2n gamete formation using band configurations and microsatellite DNA allele counting peak ratios (MAC-PR). The results showed that 2n gametes originated from the maternal rubber tree clone GT1, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
3
0
2

Year Published

2017
2017
2023
2023

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 10 publications
(5 citation statements)
references
References 37 publications
0
3
0
2
Order By: Relevance
“…Further application of these polyploid was not reported. Although triploid clones Yunyan 77-2 and Yunyan 77-4 have been selected from the natural rubber trees population and were reported in 2009 by Li et al [4], no efforts had been made to understand the mechanism of triploid until Yao et al [11] reported that rubber tree clone GT 1 can produce 2n megagametophyte spontaneously, which will provide reasonable guidance for polyploid induction using 2n gametes.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Further application of these polyploid was not reported. Although triploid clones Yunyan 77-2 and Yunyan 77-4 have been selected from the natural rubber trees population and were reported in 2009 by Li et al [4], no efforts had been made to understand the mechanism of triploid until Yao et al [11] reported that rubber tree clone GT 1 can produce 2n megagametophyte spontaneously, which will provide reasonable guidance for polyploid induction using 2n gametes.…”
Section: Discussionmentioning
confidence: 99%
“…Yunyan 77-2 and Yunyan 77-4 both were selected from GT 1 (Gondang Tapen, Indonesia) × PR 107 (Profestation voor Rubber, Indonesia) [9,10]. Yao et al [11] has proved that rubber tree clone GT 1 is able to produce 2n megagametophyte spontaneously. At present, no unreduced pollen has been reported in rubber trees.…”
Section: Introductionmentioning
confidence: 99%
“…美洲黑杨、欧洲山杨也存在可自然产生 2n配子的雌株 [31,32] . 这种由天然2n配子生产的三倍体 品种实际已经在生产中得到应用, 如我国云南广泛栽 培的"云研77-2"、"云研77-4"橡胶树三倍体品种起源 于母本"GT1"自然发生的2n雌配子 [33] . 而三倍体毛白 杨系列品种则来源于天然2n花粉授粉杂交 [8] .…”
Section: 林木三倍体选育途径及技术关键unclassified
“…The use of unreduced gametes in plant breeding has led to the establishment of sexual polyploids and has played an important role in the improvement of crops such as carnation [ 8 ], Japanese persimmon [ 9 ], lemon [ 10 ], lily [ 11 , 12 ], poplar [ 13 ], potato [ 14 ], rose [ 15 , 16 ] and rubber trees [ 17 ]. Triploids with important horticultural traits, such as vigorous growth and large flowers, were identified in tulip 2x × 2x hybrid progenies [ 18 ].…”
Section: Introductionmentioning
confidence: 99%